1993
DOI: 10.1063/1.465423
|View full text |Cite
|
Sign up to set email alerts
|

Temperature programmed desorption of molecular hydrogen from a Si(100)-2×1 surface: Theory and experiment

Abstract: New experimental temperature programmed desorption (TPD) data have been obtained under carefully controlled conditions for atomic deuterium on the single crystal Si(100)-2×1 surface. A wide range of coverages from Θ=1.5 to 0.05 ML was used. A kinetic lattice-gas model has been developed which describes atomic hydrogen (or deuterium) adsorbed on the Si(100)-2×1 surface in terms of four basic units: dihydride (SiH2), doubly occupied dimers (H–Si–Si–H), singly occupied dimers (Si–SiH), and unoccupied dimers (Si=S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
93
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(106 citation statements)
references
References 33 publications
13
93
0
Order By: Relevance
“…The quality of the surface was periodically checked with hydrogen desorption experiments, providing benchmark data that could be compared with data reported in the literature. 27 Acetone ͑Aldrich͒ was purified by long term exposure to molecular sieves ͑to remove water͒. Acetaldehyde ͑Aldrich͒ was used without further purification.…”
Section: Methodsmentioning
confidence: 99%
“…The quality of the surface was periodically checked with hydrogen desorption experiments, providing benchmark data that could be compared with data reported in the literature. 27 Acetone ͑Aldrich͒ was purified by long term exposure to molecular sieves ͑to remove water͒. Acetaldehyde ͑Aldrich͒ was used without further purification.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the fact that when the H coverage is greater than 1 ML, a sharp temperature increase is required for epitaxy, they suggested that dihydride may disrupt the dimer structure of Si(100) or act as a nucleation site which leads to surface roughening. The adverse effect of dihydride on Si homoepitaxy can be further elucidated from the observation that on HF dipped samples, epitaxy requires a growth temperature > 643 K. 6,7 This can be explained by the fact that at ~680 K most of the dihydride units on HF dipped surfaces are converted to monohydride by H 2 desortion [8][9][10] , and the monohydride surface is more apt for epitaxy (see our results in Sec. 3).…”
Section: Introductionmentioning
confidence: 99%
“…The kinetics and dynamics of hydrogen interaction with silicon surfaces have recently become a topic of extensive experimental [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] and theoretical efforts. The great interest is, of course, partly due to the importance of H/Si in semiconductor chemistry.…”
Section: Introductionmentioning
confidence: 99%